2010
DOI: 10.1080/01635580903441212
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Mushroom Intake and the Risk of Breast Cancer Based on Hormone Receptor Status

Abstract: Although many studies have documented the antitumor activities of mushrooms, the association between mushroom intake and breast cancer, defined by hormone receptor status, has received minimal empirical investigation. This study evaluated the association between mushroom intake and the risk of breast cancer according to hormone receptor status among Korean women. Mushroom intake and breast cancer risk were examined among 358 breast cancer patients and 360 cancer-free controls. Intake of mushrooms was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Various diets among the Korean population have been studied for the risk of gastric (10 studies) (Kim et al, 2002;Ko et al, 2013;Ko et al, 2009;Lee et al, 1995;Lee et al, 2003a;Nan et al, 2005;Park et al, 1998;Park et al, 2000;Wie et al, 2014;Zhang et al, 2009), colorectal (5 studies) (Ahn et al, 2006;Kim et al, 2011;Kim et al, 2003;Lee et al, 2005;Oh et al, 2005) and breast cancer (10 studies) (Cho et al, 2010;Do et al, 2007;Hong et al, 2008;Kim et al, 2009;Kim et al, 2008;Lee et al, 2007;Lee et al, 2004;Lee et al, 2003b;Shin et al, 2010;Yu et al, 2010) (Tables 1-3); the studied diet types have been mostly soy products, fruits, and vegetables. A limited number of studies were conducted for each diet.…”
Section: Resultsmentioning
confidence: 99%
“…Various diets among the Korean population have been studied for the risk of gastric (10 studies) (Kim et al, 2002;Ko et al, 2013;Ko et al, 2009;Lee et al, 1995;Lee et al, 2003a;Nan et al, 2005;Park et al, 1998;Park et al, 2000;Wie et al, 2014;Zhang et al, 2009), colorectal (5 studies) (Ahn et al, 2006;Kim et al, 2011;Kim et al, 2003;Lee et al, 2005;Oh et al, 2005) and breast cancer (10 studies) (Cho et al, 2010;Do et al, 2007;Hong et al, 2008;Kim et al, 2009;Kim et al, 2008;Lee et al, 2007;Lee et al, 2004;Lee et al, 2003b;Shin et al, 2010;Yu et al, 2010) (Tables 1-3); the studied diet types have been mostly soy products, fruits, and vegetables. A limited number of studies were conducted for each diet.…”
Section: Resultsmentioning
confidence: 99%
“…3 Recent epidemiological studies from Asia demonstrated inverse correlation between mushroom intake and gastric, gastrointestinal, and breast cancer. [4][5][6][7] Moreover, different dietary phytochemicals have demonstrated cancer chemopreventive activities in tissue culture and animal studies. 8 For example, quercetin downregulated expression of Her-2, tyrosine kinase receptor, which is overexpressed in breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study of women with histologically confirmed breast cancer has identified that daily intake and the average consumption frequency of mushrooms were inversely associated with breast cancer risk, and a strong inverse association was found in post-menopausal women, but not in premenopausal women (Hong, Kim, Nam, Kong, & Kim, 2008), which is in contrast to another epidemiological study that has suggested a decreased risk of breast cancer from mushroom consumption by pre-menopausal women (Shin et al, 2010). In this latter study, greater mushroom intake was related to lower risk of breast cancers among premenopausal women for the highest vs. the lowest quartile intake.…”
Section: Breast Cancer Studiesmentioning
confidence: 63%